2019
DOI: 10.1177/0956797618817754
|View full text |Cite
|
Sign up to set email alerts
|

Conceptually Rich, Perceptually Sparse: Object Representations in 6-Month-Old Infants’ Working Memory

Abstract: Six-month-old infants can store representations of multiple objects in working memory but do not always remember the objects’ features (e.g., shape). Here, we asked whether infants’ object representations (a) may contain conceptual content and (b) may contain this content even if perceptual features are forgotten. We hid two conceptually distinct objects (a humanlike doll and a nonhuman ball) one at a time in two separate locations and then tested infants’ memory for the first-hidden object by revealing either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…First, infants of this age have previously been shown to successfully infer agents’ goals from their preferential reaching behavior (Luo & Baillargeon, ; Woodward, ) and to make gaze predictions based on agents’ goals (Kim & Song, ; Kochukhova & Gredebäck, ), albeit with some variability (Gredebäck et al., ). Second, and most importantly, 6‐month‐olds’ ability to maintain representations of two occluded objects (in the absence of a social agent) is well understood (Káldy & Leslie, ; Kibbe & Leslie, , , in press). In these studies, infants were familiarized with two featurally distinct objects (e.g., a disk and a triangle) placed sequentially on an otherwise empty stage.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…First, infants of this age have previously been shown to successfully infer agents’ goals from their preferential reaching behavior (Luo & Baillargeon, ; Woodward, ) and to make gaze predictions based on agents’ goals (Kim & Song, ; Kochukhova & Gredebäck, ), albeit with some variability (Gredebäck et al., ). Second, and most importantly, 6‐month‐olds’ ability to maintain representations of two occluded objects (in the absence of a social agent) is well understood (Káldy & Leslie, ; Kibbe & Leslie, , , in press). In these studies, infants were familiarized with two featurally distinct objects (e.g., a disk and a triangle) placed sequentially on an otherwise empty stage.…”
mentioning
confidence: 99%
“…This method has shown that, when objects are featurally distinct, 6‐month‐old infants represent the featural identity of the object that was hidden last , looking longer when the object is revealed to have changed (Káldy & Leslie, ; Kibbe & Leslie, ). However, 6‐month‐olds consistently fail to remember the featural identity of the object that was hidden first (Káldy & Leslie, ; Kibbe & Leslie, , in press). This robust, frequently replicated signature pattern in 6‐month‐old infants’ ability to represent two sequentially hidden objects can serve as a baseline for us to examine how their representations may be impacted when one of the objects is the target of an agent's goal‐directed reach.…”
mentioning
confidence: 99%
See 3 more Smart Citations